The Simplest Way to Iodine-Doped Anatase for Photocatalysts Activated by Visible Light - Václav Štengl; Tomáš Matys Grygar (International Journal of Photoenergy)
Iodine-doped TiO2 was prepared by thermal hydrolysis of aqueous solutions of the titanium peroxo-complex, which includes no organic solvents or organometallic compounds. The synthesized samples were characterized by X-ray diffraction (XRD), Raman spectroscopy (RS), infrared spectroscopy (IR), specific surface area (BET), and porosity determination (BJH). The morphology and particle size was determined by high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED). All prepared samples have a red-shifted band-gap transition, well crystalline anatase structure, and porous particles with a 100–200 m2 g−1 specific surface area. The photocatalytic activity of iodine-doped titania samples was determined by decomposition of Orange II dye during irradiation at 365 nm and 400 nm. Iodine doping promotes the titania photocatalytic activity very efficiently under visible light irradiation. The titania sample with 0.32 wt.% I has the highest catalytic activity during the photocatalyzed degradation of Orange II dye in an aqueous suspension in the UV and visible regions.